Hybrid Cellular Nanovesicles Block PD‐L1 Signal and Repolarize M2 Macrophages for Cancer Immunotherapy - Zhao, Chenchen; Pan, Yuanwei; Liu, Lujie; Zhang, Jing; Wu, Xianjia; Liu, Yu; Zhao, Xing‐Zhong; Rao, Lang (Small (Weinheim an der Bergstrasse, Germany), 2024)
The PD1/PD‐L1 immune checkpoint blocking is a promising therapy, while immunosuppressive tumor microenvironment (TME) and poor tumor penetration of therapeutic antibodies limit its efficacy. Repolarization of tumor‐associated macrophages (TAMs) offers a potential method to ameliorate immunosuppression of TME and further boost T cell antitumor immunity. Herein, hybrid cell membrane biomimetic nanovesicles (hNVs) are developed by fusing M1 macrophage‐derived nanovesicles (M1‐NVs) and PD1‐overexpressed tumor cell‐derived nanovesicles (PD1‐NVs) to improve cancer immunotherapy. The M1‐NVs promote the transformation of M2‐like TAMs to M1‐like phenotype and further increase the release of pro‐inflammatory cytokines, resulting in improved immunosuppressive TME. Concurrently, the PD1‐NVs block PD1/PD‐L1 pathway, which boosts cancer immunotherapy when combined with M1‐NVs. In a breast cancer mouse model, the hNVs efficiently accumulate at the tumor site after intravenous injection and significantly inhibit the tumor growth. Mechanically, the M1 macrophages and CD8+ T lymphocytes in TME increase by twofold after the treatment, indicating effective immune activation. These results suggest the hNVs as a promising strategy to integrate TME improvement with PD1/PD‐L1 blockade for cancer immunotherapy. Hybrid cellular nanovesicles (hNVs) are prepared by fusing M1 macrophage‐derived nanovesicles (M1‐NVs) and PD1‐overexpressed tumor cell‐derived nanovesicles (PD1‐NVs) for enhanced cancer immunotherapy. The M1‐NVs promote the repolarization of M2‐like TAMs to M1‐like phenotype and further increase the release of pro‐inflammatory cytokines, resulting in improved immunosuppressive tumor microenvironment. Concurrently, the PD1‐NVs block PD1/PD‐L1 pathway, synergizing with M1‐NVs to boost cancer immunotherapy.